Criminal politics: beliefs, speeches, practices... knowledge and power (2011)
The exercise of the criminal policy is usually understood from a regulation perspective; however, it is possible to identify a descriptive use of the concept and assume it as an exercise of power in relation to the criminal phenomenon in which discourses